Capturing the value of peer support: measuring recovery-oriented services. Issue 3 (24th June 2019) - Barrenger, Stacey L.; Stanhope, Victoria; Miller, Emma
Abstract : Purpose: The purpose of this paper is to examine the gap between recovery-oriented processes and clinical outcomes in peer support, an exemplar of recovery-oriented services, and offer suggestions for bridging this gap. Design/methodology/approach: This viewpoint is a brief review of literature on peer support services and gaps in outcome measurement towards building an evidence base for recovery-oriented services. Findings: Clinical outcomes like hospitalizations or symptoms remain a focus of research, practice and policy in recovery-oriented services and contribute to a mixed evidence base for peer support services, in which recovery-oriented outcomes like empowerment, self-efficacy and hopefulness have more evidentiary support. One approach is to identify the theoretical underpinnings of peer support services and the corresponding change mechanisms in models that would make these recovery-oriented outcomes mediators or process outcomes. A better starting point is to consider which outcomes are valued by the people who use services and develop an evaluation approach according to those stated goals. User driven measurement approaches and more participatory types of research can improve both the quality and impact of health and mental health services. Originality/value: This viewpoint provides a brief review of peer support services and the challenges of outcome measurement in establishing an evidence base and recommends user driven measurement as a starting point in evaluation of recovery-oriented services.